2017
DOI: 10.5147/ajb.v1i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Silver Nanoparticle Ingestion on Pigmentation and Developmental Progression in Drosophila

Abstract: In recent years, the advent of nanomaterial use has increased exposure rates and raised health concerns. However, the toxicology profiles of many nanomaterials are far from complete for various reasons. In this study, Drosophila melanogaster, commonly called fruit flies, were exposed to one of the most widely used nanomaterials, silver nanopowder (Ag NP), to assess its toxicity and determine if D. melanogaster would be a good model organism for nanotoxicology studies. Comparison of developmental progression am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Cuticular pigmentation is a critical parameter of an insect’s life, as it influences various physiological and behavioral aspects, including lifespan, immunity, stress tolerance, and courtship. Loss of cuticular melanization is a well-known manifestation of AgNPs exposure in Drosophila [ 44 , 45 , 46 ]. Importantly, it was observed that the extent of loss of pigmentation in flies upon NP ingestion is directly correlated with decreased longevity, decreased locomotor activity, and overall toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cuticular pigmentation is a critical parameter of an insect’s life, as it influences various physiological and behavioral aspects, including lifespan, immunity, stress tolerance, and courtship. Loss of cuticular melanization is a well-known manifestation of AgNPs exposure in Drosophila [ 44 , 45 , 46 ]. Importantly, it was observed that the extent of loss of pigmentation in flies upon NP ingestion is directly correlated with decreased longevity, decreased locomotor activity, and overall toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that the extent of AgNP-mediated loss of melanization is proportional to the extent of system dysfunctions observed in Drosophila [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%